Neuroprotection by the Traditional Chinese Medicine, Tao-Hong-Si-Wu-Tang, against Middle Cerebral Artery Occlusion-Induced Cerebral Ischemia in Rats. (4th November 2010) - Wu, Chih-Jen; Chen, Jui-Tai; Yen, Ting-Lin; Jayakumar, Thanasekaran; Chou, Duen-Suey; Hsiao, George; Sheu, Joen-Rong
Abstract : Tao-Hong-Si-Wu-Tang (THSWT) is a famous traditional Chinese medicine (TMC). In the present study, oral administration of THSWT (0.7 and 1.4 g kg − 1 day − 1 ) for 14 days before MCAO dose-dependently attenuated focal cerebral ischemia in rats. MCAO-induced focal cerebral ischemia was associated with increases in hypoxia-inducible factor (HIF)-1α, inducible nitric oxide synthase (iNOS), tumor necrosis factor (TNF)-α, and active caspase-3 expressions in ischemic regions. These expressions were obviously inhibited by 0.7 g kg − 1 day − 1 THSWT treatment. In addition, THSWT inhibited platelet aggregation stimulated by collagen in washed platelets. In an in vivo study, THSWT (16 g kg − 1 ) significantly prolonged platelet plug formation in mice. However, THSWT (20 and 40 μ g mL − 1 ) did not significantly reduce the electron spin resonance (ESR) signal intensity of hydroxyl radical (OH ) formation. In conclusion, the most important findings of this study demonstrate for the first time that THSWT possesses potent neuroprotective activity against MCAO-induced focal cerebral ischemia in vivo . This effect may be mediated, at least in part, by the inhibition of both HIF-1α and TNF-α activation, followed by the inhibition of inflammatory responses (i.e., iNOS expression), apoptosis formation (active caspase-3), and platelet activation, resulting in a reduction in the infarct volume in ischemia-reperfusion brain injury.